Efficacy and Safety of Very Low Achieved LDL Cholesterol in Patients With Previous Ischemic Stroke. - Monguillon,V; Kelly,PJ; O'Donoghue,ML; Park,J-G; Bohula,EA; Saver,JL; Atar,D; Keech,AC; Sever,PS; Wang,H; Paiva,da Silva Lima G; Sabatine,MS; et al. (Circulation, 2026)
BACKGROUND: Patients with previous ischemic stroke are at high risk for recurrent stroke and other major adverse cardiovascular events. The benefits of achieving very low levels of low-density lipoprotein cholesterol (LDL-C) in such patients is unclear. METHODS: We analyzed patients with previous ischemic stroke enrolled in FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk), a randomized placebo-controlled trial studying evolocumab in patients with stable atherosclerotic cardiovascular disease (median follow-up, 2.2 years), and through the open-label extension (FOURIER-OLE) period (additional median follow-up, 5 years), to examine the relationship between achieved LDL-C and the long-term incidence of the primary end point (cardiovascular death, myocardial infarction, stroke, or hospitalization for unstable angina or coronary revascularization) and stroke-related end points. RESULTS: The analysis included 5291 patients with previous ischemic stroke (>4 weeks). Of these, 666 (12.6%), 1410 (26.6%), 586 (11.1%), 508 (9.6%), and 2121 (40.1%) patients achieved LDL-C values of <20, 20 to <40, 40 to <55, 55 to <70, and ≥70 mg/dL, respectively. The incidence of the primary end point, all stroke, and ischemic stroke each decreased in a monotonic fashion with lower achieved LDL-C levels on a continuous scale (Ptrend<0.001, 0.002, and 0.002, respectively). Compared with patients with LDL-C ≥70 mg/dL, those who achieved levels <40 mg/dL had incidence rate ratios of 0.69 (95% CI, 0.57-0.84), 0.73 (95% CI, 0.53-0.99), and 0.75 (95% CI, 0.54-1.05) for the outcomes of the primary end point, all stroke, and ischemic stroke, respectively. Hemorrhagic strokes were infrequent and unrelated to achieved LDL-C (Ptrend=0.85). CONCLUSIONS: In patients with previous ischemic stroke, it appeared that the lower the LDL-C, down to levels <40 mg/dL, the lower the risk of major adverse cardiovascular events, includi